Effect of time delay in centrifugation and centrifugation immediately on the stability of triglyceride levels in blood samples - Mustika Hutabarat (Universitas Hang Tuah, 2023)
Background : Triglyceride examination was carried out in three stages, namely pre-analytical, analytical, and post-analytical stages. The pre-analytical stage of specimen processing is one of the factors that can affect triglyceride levels. However, in the field are often that the processing for triglyceride test specimen examination oftenis not in accordance with applicable regulations. Method : This research is a pre-experimental research design with intact Group Comparison. The research subjects used were 30 TLM students. Blood samples were collected in 2 clot activator tubes, then the first tube was immediately centrifuged and the second tube was left for 30 minutes before being centrifuged. Results : The results showed that the average triglyceride level in the blood that immediately centrifuged was heigher than the blood that was left for 30 minutes before being centrifuged. There for, It is stated that there is a significant difference in the p value = 0.001 (p<0.05). Conclusion : Based on the research, it was concluded that there was a significant difference in the examination of triglyceride levels. Between blood sample that was immediately centrifuged and the blood that was left for 30 minutes before being centrifuged.